Diversidade genética e eficiência simbiótica de estirpes de bactérias que nodulam feijão-caupi isoladas de solos sob cultivo agrícola na Amazônia Ocidental - Guimarães, Amanda Azarias (2009)
The objective of this study was to evaluate the genetic and symbiotic diversity of nitrogen-fixing cowpea nodulating bacteria from agricultural soils under cultivation in the Western Amazon. These isolates were obtained in a previous work from a collection of 1010 strains, comprising different land used systems origin. First of all, they were transferred to Petri dishes containing medium 79, to check their cultural characteristics previously described. One hundred nineteen out of 158 isolates from agriculture were obtained in pure culture. Authentication and symbiotic efficiency experiments of those isolates were made in a greenhouse, with a completely randomized desing and three repetitions. We used recycled "long neck" bottles (500mL) containing Hoagland solution diluted four times and cowpea as a host plant (cultivar BR17 Gurguéia). Two control treatments without inoculation (with and without mineral nitrogen) and another three positive controls with strains commercial inoculant strains INPA 03-11B, UFLA 03-84, BR 3267 were used. The authentication was evaluated through nodules presence (+) or absence (-) in inoculated plants. The symbiotic efficiency was evaluated 35 days after emergence when the nodules number, nodules dry weight, shoot dry matter weight and relative efficiency were determined. The data were subjected to analysis of variance and mean comparison by the Scott Knott test in a probability of 5%. The 62 isolates with positive nodulation were submitted to analysis of DNA polymorphism in order to assess their diversity, using the BOX-PCR technique. The following type or reference strains were included in this analysis: Azorhizobium dobereinerae (BR 5401), Azorhizobium caulinodans (ORS 571T), Cupriavidus taiwanensis (LMG19424T), Burkholderia sabiae (BR3405), Mesorhizobium plurifarium (BR3804), Bradyrhizobium sp. (UFLA 03-84), Bradyrhizobium ellkanii (INPA 03-11B). Through the cultural characterization it was possible to cluster the isolates, combining the cultural characteristic; time of growth and pH changing it was obtained twelve different groups. The isolates showed variable symbiotic efficiency, 68% of isolates promoted statistically significant increasing in shoot dry matter weights regarding in the control without inoculation and without mineral nitrogen. It was found high genetic diversity with 80% of similarity. The isolates had similarity less than 65% to type strains. The results showed high symbiotic, genetic and phenotypic diversity, in agriculture areas, with potentially new species of bacteria.